Propensity score analysis of overall survival between first‐ and second‐generation EGFR‐TKIs using real‐world data. Issue 10 (5th August 2020) - Ito, Kentaro; Murotani, Kenta; Kubo, Akihito; Kunii, Eiji; Taniguchi, Hirokazu; Shindoh, Joe; Asada, Kazuhiro; Imaizumi, Kazuyoshi; Takahashi, Kosuke; Karayama, Masato; Okuno, Motoyasu; Inui, Naoki; et al.
Abstract: We constructed a data set of EGFR‐mutant non–small‐cell lung carcinoma (NSCLC) patients, and compared the overall survival of first‐generation (1G), and second‐generation (2G) EGFR‐tyrosine kinase inhibitors (TKIs) in clinical practice using a propensity score. We reviewed the clinical data of consecutive EGFR‐mutated NSCLC patients who received EGFR‐TKI therapy between January 2008 and August 2017 at 11 institutions in Japan. The primary endpoint was overall survival (OS). When comparing OS between 1G and 2G EGFR‐TKIs, propensity score analyses were performed using 2 methods: matching and inverse probability of treatment weighting (IPTW). (Clinical Trial information: UMIN000030121) In total, 1400 patients from 11 institutions were enrolled in this study, and the data from the 1366 patients who received only EGFR‐TKI therapy were analyzed (gefitinib [GEF], N  = 732; erlotinib [ERL], N  = 416; afatinib, N  = 218). Median OS times (months [95%CI]) were 29.7 [27.5‐33.5] in the 1G group (gefitinib, 32.0 [28.1‐35.8]; erlotinib, 27.5 [23.9‐31.7]), and 38.6 [32.2‐NR] in the 2G group (afatinib), respectively. The trend of longer OS for afatinib against 1G EGFR‐TKIs remained, even after adjusted by propensity score. (unadjusted, hazard ratio [HR] 0.676, P  = .0023; adjusted by IPTW, HR 0.685 P  < .0001; adjusted by matching, HR 0.725, P  = .0418). Exploratory analysis showed that OS using the 2G EGFR‐TKI was superior to that of the 1G EGFR‐TKIs, suggesting the potential of sequential therapy of 2G EGFR‐TKI followed by osimertinib. (HR 0.419, P  = .0519) Real‐world data analysis using 1354 data records, using propensity scoring, indicated that 2G EGFR‐TKI had a trend of longer OS compared with 1G EGFR‐TKIs. Abstract :